Identifying Costs and Benefits of Smart City Applications from End-users' Perspective - Mario Jadrić; Tea Mijač; Maja Ćukušić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
The widespread availability and adoption of various smart city solutions have benefited their users by providing new services and information generated in real-time. These solutions use different types of sensors and GPS to collect, process and display data within the web and/or mobile applications. Focusing on the determinants of the intentions to use an application or its success, a large number of researchers developed and validated models such as TAM, UTAUT, IS Success Model and similar ones. This paper presents an exploratory approach that is based on the cost-benefit analysis with end-users who were invited to express their perceptions of different smart city solutions. Qualitative data were collected to devise a research instrument in subsequent phases based on the feedback from second-year business students. For each of the selected four smart city applications (smart parking, water quality monitoring, air quality monitoring, and real-time traffic monitoring), respondents were asked to work in groups and create a list of benefits and costs from their perspective. The analysis resulted with the list of 98 different cost and benefit statements (16 costs common for four smart city applications, 12 benefits common for four smart city applications, 10 distinctive costs and 60 specific benefits).
Keywords: M15; 330; Smart city applications; Smart parking; Water quality monitoring; Air quality monitoring; Real-time public transit information; Integrated smart solutions; End-users perceptions; Cost-benefit analysis